Analysis of Beginning Reading Difficulties of Elementary School Class II Students - Aqmarina, Rafika; Cahyani, Isah (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This study aims to describe the difficulty of reading the beginning of the second grade students of SDN 209 Antapani. In practice this research uses descriptive qualitative research with data collection techniques used by researchers are interviews, observation, and documentation. The data analysis technique uses the Milles and Huberman model with the stages of data reduction, data presentation, and drawing conclusions. The subjects in this study were class IIA teachers and class IIA students. By paying attention to the findings and discussion, this study was able to prove that the reading ability of the second graders at SDN 209 Antapani was not good. The results showed that 30% of students who had difficulty reading the beginning. Teachers' efforts to improve early reading skills through the use of models, methods, techniques and innovative approaches, as well as learning media to support the learning process. The theoretical analysis in the discussion provides in-depth information about the early reading ability of second grade elementary school students.